Short stature, platyspondyly, hip dysplasia, and retinal detachment: An atypical type II collagenopathy caused by a novel mutation in the C-propeptide region of COL2A1: A case report - Apiruk Sangsin (2018)
© 2016 The Author(s). Background: Heterozygous mutations in COL2A1 create a spectrum of clinical entities called type II collagenopathies that range from in utero lethal to relatively mild conditions which become apparent only during adulthood. We aimed to characterize the clinical, radiological, and molecular features of a family with an atypical type II collagenopathy. Case presentation: A family with three affected males in three generations was described. Prominent clinical findings included short stature with platyspondyly, flat midface and Pierre Robin sequence, severe dysplasia of the proximal femora, and severe retinopathy that could lead to blindness. By whole exome sequencing, a novel heterozygous deletion, c.4161_4165del, in COL2A1 was identified. The phenotype is atypical for those described for mutations in the C-propeptide region of COL2A1. Conclusions: We have described an atypical type II collagenopathy caused by a novel out-of-frame deletion in the C-propeptide region of COL2A1. Of all the reported truncating mutations in the C-propeptide region that result in short-stature type II collagenopathies, this mutation is the farthest from the C-terminal of COL2A1.